X-ray measurements of thin liquid films in gas–liquid pipe flow. (October 2020) - Skjæraasen, Olaf; Kesana, Netaji R.
Highlights: Liquid film thickness profiles in gas–liquid annular flow can be reconstructed from stereoscopic X-ray data. Using X-ray data, the film thickness can be obtained at hundreds of points around the pipe perimeter. The film thickness detection limit is approximately 30 µm with the presented setup. The method is applicable to 2-phase or 3-phase systems, to horizontal or inclined pipes, and to steady or dynamic systems. Experiments have been performed with high-density SF6 gas and Exxsol D60 oil. Abstract: This paper presents a method for reconstructing the thickness profile of the thin liquid film being present in steady, fully developed gas–liquid annular pipe flow, taking advantage of nonintrusive X-ray measurements. Experiments have been performed with low liquid loading, annular flows, in a near horizontal pipe system (inclination +2.5 ° ), using a high-density gas (SF6 ) and Exxsol D60 oil. Special care was taken to ensure the flows were fully developed, and statistically steady. The superficial gas velocity was maintained at a constant value of 10 m/s, while the superficial liquid velocity was varied between 0.5 mm/s and 42 mm/s. The X-ray measurements were supplemented by gamma ray densitometer data and isokinetic data. An explicit mathematical method is presented, whereby the shape and thickness of very thin liquid films can be reconstructed if X-ray images of the flow have been obtained from two independent directions: one with a vertical view of the pipe, and another with a horizontal side view. The method can be straightforwardly applied to cases where the film volume dominates the total volume of droplets suspended in the gas phase. This condition is generally satisfied for the experiments presented in this paper, as verified by isokinetic measurements. Mean liquid hold-up values determined by gamma densitometer are in reasonable agreement with the X-ray results. It is found that the mean film thickness at any position on the pipe wall increases with the superficial liquid velocity. While the film thickness is maximal at the pipe bottom in virtually all experimental cases, its profile exhibits multiple local maxima and minima, with the smallest thickness apparently 20°–30° away from at the pipe top. The presented film reconstruction method is highly sensitive; even at extremely low liquid levels, with a superficial liquid velocity less than 0.01% of the mixture velocity, the film and its thickness profile are clearly detected. An analytical fit for the film profile as a function of perimeter angle and superficial liquid velocity is given. The fit captures the main features of the profile as derived from X-ray measurements, for thin films with maximum thickness less than 5% of the pipe diameter.